Keanekaragaman Kepiting Bakau (Scylla spp.) di Kawasan Mangrove Desa Masbangun Kecamatan Teluk Batang Kabupaten Kayong Utara - Virda Juliati Putri; Riza Linda; Etha Marista (JKP - Jurnal Kelautan dan Pesisir, 2024)
Mangrove ecosystems as a coastal resource known as an important ecological function in supporting fisheries resources and is a very potential habitat for various aquatic biota. Mangrove crab (Scylla sp.) is one of the biota that has an ecological relationship with mangrove ecosystem areas with a high enough protein content to become one type of potential marine commodity. The purpose of this study was to determine the type and diversity of mangrove crabs found in the Mangrove Area of Masbangun Village, Teluk Batang District, North Kayong Regency. Determination of observation stations using purposive sampling method based on environmental hue. The results showed that the mangrove crabs found totaled 11 individuals consisting of 2 species, namely Scylla olivacea and Scylla tranquebarica. The diversity index value is low, ranging from 0-0.63, the uniformity value is high, ranging from 0-0.81, and the dominance value is moderate, ranging from 0.55-1. Aquatic environmental factors in the study area are included in the optimal range that can affect the presence and growth of mud crabs.